2010
DOI: 10.1007/s10734-010-9355-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing college students’ perceptions of a case teacher’s pedagogical content knowledge using a newly developed instrument

Abstract: Ongoing professional development for college teachers has been much emphasized. However, previous research on learning environments has seldom addressed college students' perceptions of teachers' PCK. This study aimed to evaluate college students' perceptions of a physics teacher's PCK development using a newly developed instrument and workshop intervention. A mixed method design was employed incorporating both quantitative and qualitative techniques. The survey ''Assessing Students' Perceptions of College Tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 32 publications
2
32
0
4
Order By: Relevance
“…Science seems to be the dominating subject here, see e.g. Jang (2011), but studies are found also in other areas, for example mechanical engineering (Viiri, 2003) and industrial design (Phillips et al, 2009). …”
Section: Areas Where Pck Is Appliedmentioning
confidence: 99%
“…Science seems to be the dominating subject here, see e.g. Jang (2011), but studies are found also in other areas, for example mechanical engineering (Viiri, 2003) and industrial design (Phillips et al, 2009). …”
Section: Areas Where Pck Is Appliedmentioning
confidence: 99%
“…This cognitive constructivism implies that people tend to search for meaning while they interact with their environment, assess the situation, and modify their existing schema (Packer & Goicoechea, 2000;Piaget, 1967;Vygotsky, 1978). Therefore, students' perceptions of educational phenomena could be interpreted in the theoretical framework of cognitive constructivism, as perceptions are known to affect the way in which students actually learn or do not learn through their experiences and interactions with their environment (Haney & Bissonnette, 2011;Jang, 2011). As Hegde and Cassidy (2009) noted, individuals' perceptions influence their interpretation of events and their implementation into practice.…”
Section: Theoretical Framework: Cognitive Constructivismmentioning
confidence: 99%
“…Most university instructors entering the profession may find their initial teaching efforts stressful, but with experience, they acquire a repertoire of teaching strategies and representations that they draw on throughout their teaching. Instructors' teaching style in coping with many of the routine demands in teaching can impede their professional growth (Jang 2008(Jang , 2011. Many novice college instructors cannot be effective teachers by simply holding doctoral degrees and a certain level of knowledge for their subject matter knowledge (SMK) (Jang 2011;Major and Palmer 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Instructors' teaching style in coping with many of the routine demands in teaching can impede their professional growth (Jang 2008(Jang , 2011. Many novice college instructors cannot be effective teachers by simply holding doctoral degrees and a certain level of knowledge for their subject matter knowledge (SMK) (Jang 2011;Major and Palmer 2006). In addition to better SMK, they also need more pedagogical knowledge and skills (Leinhardt and Smith 1985;Lenze and Dinham 1994).…”
Section: Introductionmentioning
confidence: 99%